2008
DOI: 10.1007/s10103-008-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-level laser therapy modulates cyclo-oxygenase-2 expression during bone repair in rats

Abstract: The goal of this study was to analyze the role of cyclo-oxygenase-2 following bone repair in rats submitted to low-level laser therapy. A total of 48 rats underwent surgery to inflict bone defects in their tibias having been randomly distributed into two groups: negative control and laser exposed group, i.e., the animals were treated with low-level laser therapy by means of gallium arsenide laser at 16 J/cm(2). The animals were killed after 48 h, 7 days, 14 days, or 21 days. The tibias were removed for morphol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 25 publications
3
52
0
7
Order By: Relevance
“…In this context, several studies demonstrated that LLLT had a positive effect in the process of bone consolidation in experimental models in rats [9,23,24]. These findings are in line with the results of the current study, which revealed that LLLT was able to modulate the inflammatory process in the area of the bone defect and to produce an earlier deposition of granulation tissue and newly formed bone.…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In this context, several studies demonstrated that LLLT had a positive effect in the process of bone consolidation in experimental models in rats [9,23,24]. These findings are in line with the results of the current study, which revealed that LLLT was able to modulate the inflammatory process in the area of the bone defect and to produce an earlier deposition of granulation tissue and newly formed bone.…”
Section: Discussionsupporting
confidence: 95%
“…In addition, it is important to emphasize that the energy of the laser 2.8 J used in this study had a positive result on bone metabolism at the site of the injury. It is possible to find in literature a wide range of fluencies and energy of laser irradiation used by different authors on bone healing and fractures [9,23,24,40]. In a recent study, Batista et al, [46] used 830 nm laser irradiation, at 6 J, and presented a positive local biostimulative effect in the early stage of bone healing.…”
Section: Discussionmentioning
confidence: 95%
“…An additional control group, that remained empty, was included. Recently, we have applied this methodology with success in rats exposed to laser treated or not with anti-inflammatory drugs [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Os materiais de regeneração óssea têm sido testados em defeitos cirúrgicos de diferentes tamanhos, sejam em tíbia (Matsumoto et al, 2009;Fernandes et al, 2013), fêmur Weber et al, 2006) e calvária (Marques et al, 2015;Cunha et al, 2014). A evolução da cicatrização que ocorrerá é em grande parte dependente do tamanho do defeito realizado (Hjörting-Hansen, 1971;Simons, 1980).…”
Section: Modelo Experimentalunclassified
“…Até o momento, não existe consenso quanto ao melhor modo de utilização do LBI na regeneração óssea , com uma diversidade de protocolos relatada na literatura (Lopes et al, 2007;Matsumoto et al, 2009;Pereira et al 2009;Gharoudhi et al, 2014) e, também a utilização de vários modelos experimentais, com diferentes resultados (Rochkind et al,m 2004;Pereira et al, 2009;Fernandes et al, 2013;Ghahroudi et al, 2014;Marques et al, 2015).…”
Section: Grupo Média Das Diferençasunclassified